2013
DOI: 10.3928/1081597x-20131115-03
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Study of Toric IOL Outcomes When Dual Zone Automated Keratometry Is Used for Astigmatism Planning

Abstract: In this series of eyes from multiple centers, the calculation of toric IOL power using dual-zone automated keratometry measurements produced clinical results that were better than results in the literature where manual keratometry was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…88.2% of the postoperative residual astigmatism were ≤ 0.75 D and 71.8% ≤ 0.5 D. These outcomes are very similar to previous studies. Potvin et al evaluated clinical outcomes of patients whose toric IOL calculations were based on the Lenstar LS900 dual zone automated keratometer and found that 76% of eyes had ≤0.50 D of astigmatism after 3 months [14]. Results using the Barrett toric calculator show 72-80% of the cases with a residual refractive astigmatism of 0.5 D or less [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…88.2% of the postoperative residual astigmatism were ≤ 0.75 D and 71.8% ≤ 0.5 D. These outcomes are very similar to previous studies. Potvin et al evaluated clinical outcomes of patients whose toric IOL calculations were based on the Lenstar LS900 dual zone automated keratometer and found that 76% of eyes had ≤0.50 D of astigmatism after 3 months [14]. Results using the Barrett toric calculator show 72-80% of the cases with a residual refractive astigmatism of 0.5 D or less [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…IOLs [8], and reported lens tilt [9]. Several diagnostic devices based on different technologies are available to measure preoperative corneal power and astigmatism, including manual and automated keratometers; Placido-based corneal, point-source color light emitting diode, Scheimpflug imagebased, and scanning-slit corneal topographers; low-coherence reflectometers; and intraoperative aberrometers [10][11][12][13]. However, none of these methods are currently considered the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Manual keratometry, optical low-coherence reflectometry (OLCR), partial coherence interferometry (PCI), and topographers have traditionally been used for measuring the curvature of the eye’s anterior surface to determine the power and axis of toric IOLs. 10 Total corneal power (TCP) and astigmatism were calculated based on the assumptions that there exists a fixed ratio between the anterior and posterior curvatures and that the minimal refractive power of the posterior surface is inconsequential. However, a discrepancy was observed between results obtained through different modalities.…”
Section: Introductionmentioning
confidence: 99%